Efforts to Improve Hand-Eye Coordination in Children Aged 4–5 through Sensorimotor Games at PAUD Anak Bangsa Palembang - Oktarina, Saniyyah; Andika, Windi Dwi (Journal of English Language and Education, 2025)
This study aims to improve hand-eye coordination in 4–5-year-old children through sensorimotor games at PAUD Anak Bangsa Palembang. Using Classroom Action Research (CAR) in two cycles, the first cycle applied meronce and the second used puzzles. The subjects were 12 Group A children. Data were gathered through observation, interviews, and documentation. Results showed improved hand-eye coordination across cycles, with significant progress during puzzle activities. In the first cycle, improvements were visible but still in the early stages. In contrast, the second cycle showed more optimal development. Thus, sensorimotor games like bead-stringing and puzzles effectively enhance hand-eye coordination in early childhood learning activities.